Multiple Criteria Decision Analysis: State of the Art Surveys - Greco, Salvatore (International Series in Operations Research & Management Science,, 2005)
MULTIPLE CRITERIA DECISION ANALYSIS: State of the Art Surveys is the most comprehensive work available to survey the state of the art in MCDA to date. Its 24 chapters are organized in eight parts and are written by 49 international leading experts. Each of these parts covers one of the central streams of multiple criteria decision analysis literature. These literature streams are: MCDA today, Foundations of MCDA, Outranking Methods, Multiattribute Utility Theory, Non-Classical MCDA Approaches, Multiobjective Mathematical Programming, Applications, and MCDM Software. The handbook presents the most up-to-date discussions on well-established methodologies and theories in the field, while systematically surveying emerging fields in MCDA such as conjoint measurement, fuzzy preferences, fuzzy integrals, rough sets, etc. MULTIPLE CRITERIA DECISION ANALYSIS is a valuable reference volume (more than 2000 references) for the field of decision analysis. It provides graduate students, researchers, and practitioners with a sweeping survey of MCDA theory, methodologies, and applications. It is a handbook that is particularly suitable for use in seminars in Decision Analysis, Decision Support, and Decision Theory.